EKSISTENSI AKAD DALAM TRANSAKSI KEUANGAN SYARIAH - Alim Mumin, Muh. Dian Nur; Kurniadi, Kurniadi; Atma , A. M. (Yayasan Nuraini Ibrahim Mandiri, 2024)
This research discusses the crucial role of the existence of contracts in sharia financial transactions and the impacts they produce. One important aspect is that in Islam, there is freedom to carry out a contract by determining all the terms and forms desired by the parties involved, as long as the implementation is voluntary and does not involve things prohibited by the Shari'a. This research uses a descriptive qualitative method with a library research approach. Based on the principles explained above, the essence of a contract in Islam is to achieve benefit for all parties involved in a sharia financial transaction agreement. This research aims to find out how important an agreement or will is that has been regulated in Islam.